2019
DOI: 10.1016/j.bbmt.2018.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Hematopoietic Cell Transplantation in Patients Aged 50Years or Older with Severe Aplastic Anemia

Abstract: We report on 499 patients with severe aplastic anemia aged ≥ 50years who underwent hematopoietic cell transplantation (HCT) from HLA-matched sibling (n = 275, 55%) or HLA-matched (8/8) unrelated donors (n = 187, 37%) between 2005 and 2016. The median age at HCT was 57.8 years; 16% of patients were 65 to 77years old. Multivariable analysis confirmed higher mortality risks for patients with performance score less than 90% (hazard ratio [HR], 1.41; 95% confidence interval [CI], 1.03 to 1.92; P = .03) and after un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Our study revealed ECOG score was an independent prognostic factor for survival after HSCT in 40 years old and older SAA patients. Physical status was confirmed by several other studies to be a factor associated with outcomes after HSCT . Besides, heavily pretreated sufferings and repeated transfusion might also lead to the impaired organ function and worsen the physical status.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our study revealed ECOG score was an independent prognostic factor for survival after HSCT in 40 years old and older SAA patients. Physical status was confirmed by several other studies to be a factor associated with outcomes after HSCT . Besides, heavily pretreated sufferings and repeated transfusion might also lead to the impaired organ function and worsen the physical status.…”
Section: Discussionmentioning
confidence: 54%
“…Physical status was confirmed by several other studies to be a factor associated with outcomes after HSCT. 8,27,28 Besides, heavily pretreated sufferings and repeated transfusion might also lead to the impaired organ function and worsen the physical status. This suggested that patients should receive HSCT in good performance status and would probably benefit from an upfront HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…27 As OS of patients with SAA transplanted using MSD and MUD now exceeds 80%, evaluation of outcomes that take into account not only failurefree survival but also GVHD becomes the optimal assessment tool. 26,27 Despite a higher risk for GVHD in older transplanted patients in the reported literature, 24 we show that FCC conditioning is as effective as in younger patients at reducing the risk for GVHD, and significantly lower than other groups using predominantly ATGbased settings. 18,24 The low sample size and retrospective nature of study remains a drawback to this study.…”
Section: Discussionmentioning
confidence: 52%
“…26,27 Despite a higher risk for GVHD in older transplanted patients in the reported literature, 24 we show that FCC conditioning is as effective as in younger patients at reducing the risk for GVHD, and significantly lower than other groups using predominantly ATGbased settings. 18,24 The low sample size and retrospective nature of study remains a drawback to this study. The study lacks the power to detect small differences in survival between the 2 groups.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation